Re-imagining futures of universities of technology - Garraway, James; Winberg, Chris (Critical Studies in Teaching and Learning, 2023)
Universities of Technology in South Africa emerged relatively recently from technical college-like institutions, known as Technikons. Technikons had a distinct workplace-oriented identity, while Universities of Technology lack such clarity of identity. This paper thus explores the vexing question of what constitutes the identity of Universities of Technology. In conducting the exploration, the researchers drew on Activity Theory to structure the exchange of ideas and narratives about what a future University of Technology might be. In so doing, the researchers discovered fundamental contradictions between current practices and the desirable vision. The most significant contradictions were, firstly, between the rigid, rule-bound culture and the projected need for greater organisational flexibility, and secondly between the current, highly-boundaried university to one that should embrace intra- and inter-organisational collective action. The researchers conclude that the resolution of these contradictions could chart the way forward for reimagining the identity of a University of Technology.